2011
DOI: 10.1128/aem.01473-10
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bacteroidales Diversity and Decay in Response to Variations in Temperature and Salinity

Abstract: Bacteroidales are attractive as water quality indicators because of their potential to discern sources of fecal pollution, and it is presumed that these bacteria do not multiply outside their host organisms. The persistence of a fecal Bacteroidales marker was monitored over 14 days in river water microcosms that varied in temperature from 10°C to 30°C and salinity from 0‰ to 30‰ by quantitative PCR (qPCR). Decay rates were estimated and compared to the results of other studies examining the survival and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
(51 reference statements)
2
44
0
Order By: Relevance
“…Therefore, the question beckons how to interpret and compare data from these different experimental setups to understand decay rates of fecal pollution indicators and source identifiers in impaired water. As Schulz and Childers proposed, a repository database of raw survival and persistence data is needed for a statistical comparison of decay rates from different studies (35). Additionally, comparable kinetic studies are necessary considering inoculum effect, temperature, salinity, quantification methods, and viability of target organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the question beckons how to interpret and compare data from these different experimental setups to understand decay rates of fecal pollution indicators and source identifiers in impaired water. As Schulz and Childers proposed, a repository database of raw survival and persistence data is needed for a statistical comparison of decay rates from different studies (35). Additionally, comparable kinetic studies are necessary considering inoculum effect, temperature, salinity, quantification methods, and viability of target organism.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional fecal indicators to monitor recreational water quality are often not associated with health risks in ambient water where nonpoint sources are dominant fecal contributors, and these results suggest a need for alternative indicators of water quality (47). Furthermore, FIB are inadequate to identify the source of fecal pollution because they are observed in both warm-and cold-blooded animal feces (30,35). Microbial source tracking (MST) can discriminate between human and nonhuman fecal contamination such as cow, dog, and pig in water using microbiological or chemical traits of source identifiers (19,22).…”
mentioning
confidence: 96%
“…Temperature has also been shown to correlate strongly with inactivation of Bacteroidales spp. in water microcosms (19)(20)(21)(22)(23). Positive correlations between moisture and FIB concentrations have been documented in several studies (12,(24)(25)(26)(27), but an overall negative relationship between moisture and Escherichia coli (14) has been reported.…”
mentioning
confidence: 99%
“…It has been suggested that qPCR methods can be used to allocate fecal contributions from various hosts to degraded water quality by comparing the relative abundances of different host-specific Bacteroides markers and the total Bacteroidales abundance (17,18). For accurate source apportionment to occur, one needs to understand both the abundance of Bacteroides bacteria in host feces and the survival of these host-specific microbial markers after deposition in the environment.…”
mentioning
confidence: 99%
“…As such, many studies were undertaken recently to assess persistence and decay of host-specific Bacteroides markers in freshwater (13,(19)(20)(21)(22)(23), marine waters (11,12,17,24,25), manure-amended soils (26,27), and animal feces (9), under a variety of conditions. In general, studies have reported a positive relationship between Bacteroidales decay rates and temperature (17,20), a negative relationship between salinity and decay rates (17,25), and a variable relationship between decay rates and the presence or absence of light (13,28). Given that Bacteroidales is a deeply divergent order based on 16S rRNA gene phylogeny, it is not surprising that different Bacteroidales clades may have differing environmental persistences after leaving the intestines of warm-blooded animals in fecal material.…”
mentioning
confidence: 99%